M/F ratios of four different closing loops: 3D analysis using the finite element method (FEM) - Safavi Mohammad Reza; Geramy Allahyar; Khezri Amir Kamyar (Sciendo, 2023)
It has been claimed that the opus loop is capable of delivering a constant and optimum M/F ratio without the need for gable bends.